Efficacy of platelet-rich plasma lysate in the treatment of patients with post-traumatic eyelid scarring: an overview of clinical cases - I. A. Filatova; Yu. A. Pavlenko; S. A. Shemetov; E. V. Fedoseeva; I. N. Ponomarev; N. V. Borovkova (Российский офтальмологический журнал)
Purpose: to evaluate the effectiveness of platelet-rich plasma lysate (PRP) in the treatment of patients with post-traumatic eyelid scarring by clinical examples. Material and methods. Patients with post-traumatic scarring changes in eyelid tissues causing a damage in the functional and cosmetic state of the auxiliary apparatus of the eye were treated in the Department of Plastic Surgery and Eye Prosthetics at the Helmholtz National Medical Research Center of Eye Diseases. Two of the patients, who had been traumatized shortly before the examination and one patient who had rejected surgery were offered treatment by PRP lysate manufactured at the Sklifosovsky Medical Research Institute of Emergency Medicine. After local infiltration anesthesia, each patient received a single injection of PRP lysate (2 ml) into the scar tissue. The result was evaluated at a follow-up that took place 3 months after the injection. Results. The clinical picture of the three patients showed a pronounced positive dynamic of the functional and cosmetic state of the auxiliary eye apparatus, which made the patients reject subsequent (additional) surgical treatment. Conclusion. An improvement tissue repair and regeneration processes after PRP lysate injection allows us to assess this method as an applicable alternative of reconstructive operations in certain cases.